Edukasi Epidemiologi Hipertensi Berbasis Sistem Informasi Geografis (SIG) Dan Pencegahan Hipertensi Di Kelurahan Bandarharjo Kota Semarang - Silvia Nurvita; Siti Noor Chotimah; Ratih Kumala Dewi; Viny Natalia Dewi; Aerrosa Murenda Mayadilanuari; Dody Indra Sumantiawan (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
Hypertension is a serious public health problem, with a significant contribution to global mortality and disability rates. This disease is predicted to continue to increase in the next few years. The aim of this study was to increase the understanding about hypertension and its prevention. The use of Geographic Information Systems (GIS) is important in mapping and treating this disease. Through community service activities in Bandarharjo Village, knowledge about hypertension and prevention efforts can be increased. Discussion method as well as leaflet distribution have proven effective in increasing public understanding about hypertension. Evaluation of the activity showed an increase in participants' knowledge, confirming the importance of this approach in public health education. It is hoped that this activity can have a positive impact in the long term by increasing awareness and preventive measures for hypertension in the community.